Knowledge translation following the implementation of a state-wide Paediatric Sepsis Pathway in the emergency department- a multi-centre survey study - Amanda Harley; Luregn J. Schlapbach; Paula Lister; Debbie Massey; Patricia Gilholm; Amy N. B. Johnston (BMC, 2021)
Abstract Background Several health care systems internationally have implemented protocolised sepsis recognition and treatment bundles for children to improve outcomes, as recommended by the Surviving Sepsis Campaign. Successful implementation of clinical pathways is challenging and dependent on nurse engagement. There is limited data on knowledge translation during implementation of sepsis quality improvement programs. Methods This cross-sectional, multicentre observational survey study evaluated knowledge and perceptions of Emergency Department nurses in relation to the recognition, escalation and management of paediatric sepsis following implementation of a sepsis pathway. The study was conducted between September 2019 and March 2020 across 14 Emergency Departments in Queensland, Australia. The primary outcome was a sepsis knowledge score. An exploratory factor analysis was conducted to identify factors impacting nurses' perceptions of recognition, escalation and management of paediatric sepsis and their association with knowledge. Using a logistic mixed effects model we explored associations between knowledge, identified factors and other clinical, demographic and hospital site variables. Results In total, 676 nurses responded to the survey and 534 were included in the analysis. The median knowledge score was 57.1% (IQR = 46.7-66.7), with considerable variation observed between sites. The exploratory factor analysis identified five factors contributing to paediatric sepsis recognition, escalation and management, categorised as 1) knowledge and beliefs, 2) social influences, 3) beliefs about capability and skills delivering treatment, 4) beliefs about capability and behaviour and 5) environmental context. Nurses reported strong agreement with statements measuring four of the five factors, responding lowest to the factor pertaining to capability and skills delivering treatment for paediatric sepsis. The factors knowledge and beliefs, capability and skills, and environmental context were positively associated with a higher knowledge score. Years of paediatric experience and dedicated nurse funding for the sepsis quality improvement initiative were also associated with a higher knowledge score. Conclusion Translation of evidence to practice such as successful implementation of a sepsis care bundle, relies on effective education of staff and sustained uptake of protocols in daily practice. Our survey findings identify key elements associated with enhanced knowledge including dedicated funding for hospitals to target paediatric sepsis quality improvement projects.